The propagator for a charged oscillator with a time-dependent mass in a time-varying electromagnetic field - Dutra, Alvaro de Souza [UNESP]; de Souza, Carlos Farina; de Albuquerque, Luiz Claudio (Elsevier, 1991)
We make a change of variables and a time reparametrization in the Schrödinger equation in order to obtain the propagator of a charged oscillator with a time-dependent mass and frequency under the influence of time-varying electric and magnetic fields, in terms of the simple propagators of harmonic oscillators with constant frequencies and masses. We also discuss the Jackiw transformation and others as a particular case of ours. © 1991.